PERSEPSI PENDIDIK DAN TENAGA KEPENDIDIKAN PENDIDIKAN ANAK USIA DINI (PTK-PAUD) TERHADAP KONSEP PAUD DAN KELEMBAGAAN PAUD - Afia Rosdiana (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2007)
Based on the problems found in the field, the research was aimed at finding the perception of the teachers and education personnel of the early childhood education towards the concept and organizations of early childhood education. The population of the research covered the teachers and education personnel of the early childhood education in Yogyakarta City. The analysis result shows that the perception of the teachers and education personnel of the early childhood education towards the concept and organizations of early childhood education is in line with the concept of early childhood education. But, the practice of the early childhood organization is not in line with their concepts of early childhood education.